PARADIGMA STRATEGI PENINGKATAN KUALITAS PERPUSTAKAAN DAERAH YANG REPRESENTASIF DI KOTA BEKASI - Andi Sopandi (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2012)
In the realm of Islam, the word library is known as “maktabah” derived from “kitab” means the book. In America and Europe, the word “library” taken from the Latin “liber” means the book. There is a similar term “bibliography”, which is in the library called catalogue. In Bahasa, the word library (perpustakaan) is taken from the Sanskrit to refer to the book. Library has been part of human life. Therefore, the issue of library development is inseparable from commitment, facilities, collections, resources, budget and technology and government policy. Local library is often in a poor condition viewed as an object that is less liked by the students, especially by business people. As a result, it’s not surprising if students described library as a "spooky" or "haunted" place. Also, when students are asked how often they visit library in a month, the answer is “sometimes or never at all”. The efforts to develop and improve the quality of local libraries in Bekasi, can not be separated from a shared commitment to both government and its officials, community and business / industry to build the whole person not just imposed on educational institutions